"Universal Calculator" For Solving Physical Problems (Open Academia: Journal of Scholarly Research, 2025)
The article discusses the program "Universal Calculator" designed to solve physics and mathematics problems using a computer. The program is written in Visual Basic using numerical methods and is capable of drawing graphs of any function, solving quadratic, transcendental and differential equations of any form, as well as systems of linear equations, calculating definite integrals, determining the spectral composition of periodic functions, and processing experimental results using the "Least Squares" method.